2016
DOI: 10.18290/rpsych.2016.19.4-6en
|View full text |Cite
|
Sign up to set email alerts
|

Need-appeals, benefit-appeals, and brand-user-trait-appeals in television advertising: A content analysis of commercials

Abstract: The aim of the exploratory study was to answer the question of which categories of needs domi-nate in television commercials of material products in Poland, which of the activated needs make up clusters in the light of marketing practice, which of the benefits offered the most frequently accompany the arousal of different categories of needs, and what are the most important correlates of activated needs from the perspective of design features and scenarios of advertising. A content analysis of a sample of 418 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It turned out that the positive attributes of TBU (sophistication and responsibility) are positively related to masstige. An explanation may be that all these traits explain people's need for respect from other people to a similar extent (Gorbaniuk et al, 2016). Furthermore, we confirmed that boorishness was negatively associated with masstige severity.…”
Section: Discussionmentioning
confidence: 99%
“…It turned out that the positive attributes of TBU (sophistication and responsibility) are positively related to masstige. An explanation may be that all these traits explain people's need for respect from other people to a similar extent (Gorbaniuk et al, 2016). Furthermore, we confirmed that boorishness was negatively associated with masstige severity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively weak effects resulting from a single exposure of the manipulation, these results confirm the possibility of creating a message in the form of a general message relating to the consumer's personal qualities, which can activate existing deficiencies in self-concept. Previous research (Gorbaniuk et al, 2016; has confirmed that TV ads and tangible products of specific brands have the symbolic potential to complement each other. Advertisements convey what a brand's TBU represents, in turn, this information automatically triggers a loop of comparisons between the consumer's self-concept and the features of the TBU perceived in the advertisement.…”
Section: Managerial Implicationsmentioning
confidence: 83%
“…They found that a higher sense of congruence between one's self-image and TBU image, translates into purchase intention (Landon, 1974;Zogaj et al, 2021), product evaluation and brand loyalty (Kressmann et al, 2006), satisfaction and commitment (Japutra et al, 2021) and brand preference (Aguirre-Rodriguez et al, 2012). In other studies, it has been shown that traits associated with the TBU image are associated with various needs, including the need for security (Gorbaniuk et al, 2016). The vast majority of studies on congruence theory have been cross-sectional correlational studies that have focused on finding moderators of congruence between consumer self-image and TBU (Aguirre-Rodriguez et al, 2012).…”
Section: Introductionmentioning
confidence: 96%